"ABOVE AND BEYOND THE MARKET": the family, social reproduction, and conservatism in bernard stiegler's politics of work. Issue 6 (2nd November 2021) - Turner, Ben
Abstract: Assessments of the impact of automation often emphasize the need to "denaturalize" work. To what extent is denaturalization successful in separating proposals regarding the future of work from existing assumptions about its value? This article will explore this question by reading Bernard Stiegler's politics of work in the context of his understanding of the family. It will demonstrate that while he denaturalizes work he also naturalizes background assumptions regarding its relationship to social reproductive labor by claiming that the latter is "above and beyond the market." This gesture reproduces gendered assumptions about the nature of work and fails to provide a critical account of the changing relationship between work, the family, and economic responsibility under neoliberalism. It will be concluded that Stiegler's conservative approach to the relationship between work and the family shows that avoiding the unwitting naturalization of existing assumptions regarding work is a central problem for post-work critics.